Pengaruh Aplikasi Catatan Keuangan, Motivasi Menabung, Dan Pengetahuan Dasar Akuntansi Terhadap Disiplin Keuangan Gen Z Depok: The Influence of Financial Record Applications, Saving Motivation, and Basic Accounting Knowledge on Financial Discipline of Gen Z Depok - Magali Ilana Meta; Inaya Aidella; Restu Novi Safitri; Athiyyah Mutiara Akbar; Safina Indi Yanti; Rudianto Rudianto (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Abstracts – Gen Z members between the ages of 18 and 25 who have used personal financial applications were given an online survey to complete in order to gather quantitative data. This study looked at how basic accounting knowledge, financial tracking applications, and encouragement to save affected Gen Z's financial discipline in Depok. Multiple linear regression analysis was applied to determine the partial and simultaneous effects of the independent variables on financial discipline. The findings indicate that the use of financial tracking applications assists users in understanding their spending patterns and managing budgets in a more systematic manner. Saving motivation was also found to have a positive and significant effect, suggesting that both intrinsic and extrinsic motivations play an important role in shaping consistent financial behavior. Moreover, basic accounting knowledge supports more rational financial decision-making through proper recording, evaluation, and monitoring of financial activities. Overall, the results demonstrate that financial tracking applications, saving motivation, and basic accounting knowledge simultaneously have a significant impact on improving the financial discipline of Generation Z in Depok City. These findings highlight the importance of digital literacy, financial education, and behavioral motivation in encouraging responsible financial management among young people.